Supasorb Adsorbents for Treatment of Dyespolluted Wastewater - Saiful Azhar, Saad; Khairul Nizar, Ismail, Dr.; Mohamed Zulkali, Mohamed Daud, Assoc. Prof. Dr.; Farizul Hafiz, Kasim; Suhardy, Daud; Mohd Nazri, Salleh; Salsuwanda, Selamat; Che Zulzikrami Azner, Abidin (Malaysian Invention and Design Society (MINDS), 2010)
Saiful Azhar Saad and his team won bronze for Palm Composite: Composite Products from Palm Ash Waste. ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur